Ocorrência de Molossops brachymeles mastivus Thomas, 1911, no Brasil (Chiroptera, Molossidae) - Uieda, Wilson; Taddei, Valdir Antonio [UNESP] (Instituto Nacional de Pesquisas da Amazônia, 1980)
The present note records the free-tailed bat. Molossops brachymeles mastivus, in northern Brazil. The bat. an adult male, was captured in a buriti palm (Mauritia sp.) in Manaus( Amazonas. Brazil. Measurements are given and compared to those of adult male specimens of Molossops brachymeles cerastes, from southeastern Brazil. Apparently, this paper is the first record of M. brachymeles mastivus since the original description.

A presente nota registra a presença do morcego de cauda livre, Molossops brachymeles mastivus no norte do Brasil. O morcego, um macho adulto, foi capturado numa palmeira de buriti (Mauritia sp.) em Manaus, Amazonas. As medições são dadas e comparadas com as de machos adultos de Molossops brachymeles cerastes do sudeste brasileiro. Este trabalho é aparentemente o primeiro registro de M. brachymeles mastivus após a descrição original.